The Influence of the Outdoor Study Method on Cognitive Learning Outcomes in Science Subjects for Class IV Elementary School Students - Mufida, Izatum; Nya abelia Fitri; Taqiyya Fitri azzahra; Dwi Rahayu Irfani (Journal of Practice Learning and Educational Development, 2026)
The research focuses on the use of outdoor study methods on student learning outcomes in science subjects. The limited learning methods carried out by teachers in the classroom make students feel bored, especially at SDN Pucangrejo, this makes the learning outcomes of students, especially in class IV SDN Pucangrejo in science and science subjects less than optimal, this is because teachers still use monotonous learning methods. Students are not active when learning takes place. Therefore, this research aims to determine the effect of the outdoor study method on the cognitive learning outcomes of grade IV science and science subjects at SDN Pucangrejo which are valid and suitable for use in learning. This research uses quantitative methods with a pre-experimental design model in the realm of one group pretest-posttest design. The population with the same sample uses all class IV students at SDN Pucangrejo FY 2023/2024 with a total of 28 students. Based on the data analysis used is the paired sample t-test, the results obtained from testing the Lower and Upper data are negative or Sig. (2-tailed) = 0.000 < 0.05, so Ho is rejected and Ha is accepted, which means there is a difference before and after applying the outdoor study method. So, it can be concluded that there is an application of the outdoor study method to the cognitive learning outcomes of science and science subjects for class IV students at SDN Pucangrejo.